Photochemical Reactions of Sodium Nitroprusside in Presence of Bicarbonate Ions - J. VYAS, PIYUSH; MEHTA, MUKESH; B. PUNJABI, PINKI (Asian Journal of Chemistry, 2010)
Cyanide ligand (a strong ligand) present in sodium nitroprusside is not so easily replaced chemically. An effort has been made to replace this ligand by another anionic ligand like bicarbonate (a weak ligand). The rate of this photochemical exchange reaction has been observed spectrophotometrically. The effects of different parameters like pH, light intensity, concentration of sodium nitroprusside and bicarbonate ligand,concentration on the rate of this substitution reaction have been studied. An effort was made to isolate the product and characterize it. A tentative mechanism for this photochemical substitution reaction has been proposed.